2015
DOI: 10.1111/1750-3841.12901
|View full text |Cite
|
Sign up to set email alerts
|

Oil‐in‐Water Emulsion Exhibits Bitterness‐Suppressing Effects in a Sensory Threshold Study

Abstract: Little is known about how emulsion characteristics affect saltiness/bitterness perception. Sensory detection and recognition thresholds of NaCl, caffeine, and KCl in aqueous solution compared with oil-in-water emulsion systems were evaluated. For emulsions, NaCl, KCl, or caffeine were dissolved in water + emulsifier and mixed with canola oil (20% by weight). Two emulsions were prepared: emulsion 1 (viscosity = 257 cP) and emulsion 2 (viscosity = 59 cP). The forced-choice ascending concentration series method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Some studies (Adhikari et al ., ; Sacks et al ., ) utilized ten to twelve panellists to evaluate sensory threshold of odour and flavour. As individual variations such as age, gender and race of the panellists affect the threshold results (Mojet et al ., ; Torrico et al ., ), results from this study should not be generalized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies (Adhikari et al ., ; Sacks et al ., ) utilized ten to twelve panellists to evaluate sensory threshold of odour and flavour. As individual variations such as age, gender and race of the panellists affect the threshold results (Mojet et al ., ; Torrico et al ., ), results from this study should not be generalized.…”
Section: Methodsmentioning
confidence: 99%
“…NaCl concentration at 0.03 mM was selected because the salty taste is not recognisable at this concentration for most people (Wise & Breslin, 2013). Many studies also reported the detection threshold (the lowest stimulus concentration capable of producing a sensation without recognisable taste; Meilgaard et al, 2007) of NaCl between 3.42 and 15 mM (Paulus & Haas, 1980;Gomez et al, 2004;Piovesana et al, 2013;Torrico et al, 2015), which is much above 0.03 mM in water. Therefore, 0.03 mM NaCl was chosen to determine whether soy sauce odour could induce recognisable salty taste of NaCl in water.…”
Section: Samples Preparation For Threshold Analysismentioning
confidence: 99%
“…Five working solutions of picrocrocin (2, 4, 6, 10, 14 mg/L) were prepared by dilution from a stock solution of 36 mg/L. Subjects determined taste detection and recognition thresholds of picrocrocin using the AFC of Limits (ASTM ; Torrico and others ) at 25 ± 2 °C. In addition, they were asked to describe the taste of picrocrocin.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the recognition threshold of NaCl (0.047-0.050 g/100 mL) was lower than those of KCl (0.0822-0.107 g/100 mL). [58] It resulted in a higher impact of NaCl at the same concentration according to the taste activity concept. [59] The data from Table 6 showed that Cl -was the limiting ion for computing a balanced chemical equation.…”
Section: Saltiness Enhancing Compoundsmentioning
confidence: 99%